First detection of fluorine on Mars: Implications for Gale Crater's geochemistry. Issue 4 (25th February 2015) - Forni, Olivier; Gaft, Michael; Toplis, Michael J.; Clegg, Samuel M.; Maurice, Sylvestre; Wiens, Roger C.; Mangold, Nicolas; Gasnault, Olivier; Sautter, Violaine; Le Mouélic, Stéphane; Meslin, Pierre‐Yves; Nachon, Marion; et al.
Abstract Volatiles and especially halogens (F and Cl) have been recognized as important species in the genesis and melting of planetary magmas. Data from the Chemical Camera instrument on board the Mars Science Laboratory rover Curiosity now provide the first in situ analyses of fluorine at the surface of Mars. Two principal F‐bearing mineral assemblages are identified. The first is associated with high aluminum and low calcium contents, in which the F‐bearing phase is an aluminosilicate. It is found in conglomerates and may indicate petrologically evolved sources. This is the first time that such a petrologic environment is found on Mars. The second is represented by samples that have high calcium contents, in which the main F‐bearing minerals are likely to be fluorapatites and/or fluorites. Fluorapatites are found in some sandstone and may be detrital, while fluorites are also found in the conglomerates, possibly indicating low‐T alteration processes.